Intracellular Delivery of Rapamycin From FKBP Elastin-Like Polypeptides Is Consistent With Macropinocytosis - Peddi, Santosh; Pan, Xiaoli; MacKay, John Andrew (Frontiers in Pharmacology, 2018)
Rapamycin (Rapa) is a highly potent drug; however, its clinical potential is limited by poor solubility, bioavailability, and cytotoxicity. To improve Rapa delivery, our team has fused the cognate protein receptor for Rapa, FKBP12, to high molecular weight elastin-like polypeptides (ELPs). One construct, FAF, includes an FKBP domain at each termini of an ELP. In a recent report, FAF/Rapa outperformed a family of related carriers with higher tumor accumulation and efficacy. Despite apparent efficacy, an explanation for how FAF carries Rapa into cells has not been elucidated. This manuscript explores the intracellular fate of FAF in MDA-MB-468, a triple negative (ER-/PR-/HER2-) breast cancer line. Based on a lack of displacement by excess unlabeled FAF, no evidence was found for the involvement of a receptor in cell-surface binding. Cellular association showed no dose-dependent saturation at concentrations up to 100 μM, which is consistent with uptake through fluid phase endocytosis. FAF does colocalize with dextran, a marker of fluid phase endocytosis. Upon internalization, both FAF and dextran target low pH intracellular compartments similarly. Despite likely exposure to lysosomal pH and proteolytic activity, intracellular FAF is eliminated from cells with a relatively long half-life of 17.7 and 19.0 hours by confocal microscopy and SDS-PAGE respectively. A split luciferase reporter assay demonstrated that FAF delays the cytosolic access of Rapa in comparison to free drug by 30 minutes. A specific macropinocytosis inhibitor, amiloride, completely inhibits the cytosolic delivery of Rapa from FAF. Each of these results are consistent with macropinocytosis as the mechanism of cellular uptake necessary for the hand-off of Rapa from FKBP-based drug carriers like FAF to endogenous FKBP12 in the cytosol.